2016
DOI: 10.1037/lhb0000171
|View full text |Cite
|
Sign up to set email alerts
|

Talking past each other: Interviewer and child verbal exchanges in forensic interviews.

Abstract: We used sequential analysis to examine the relationship between interviewer question types, child responsiveness, and subsequent interviewer prompting in 103 forensic interviews investigating sexual abuse allegations with children (6–16 years old). Broad open-ended prompts were more likely to elicit responses (83%) than nonresponses (17%) from children, but nonresponding was more highly associated with this type of prompt than expected by chance. Closed-ended prompts elicited more responses (96%) than nonrespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 30 publications
5
46
0
Order By: Relevance
“…Alternatively, as in Agnew et al . 's () study, interviewers may have been poor at monitoring their success in eliciting information from CWID and MA children with open‐ended prompts and they may have adopted a more focused interviewing style as a result (Wolfman et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Alternatively, as in Agnew et al . 's () study, interviewers may have been poor at monitoring their success in eliciting information from CWID and MA children with open‐ended prompts and they may have adopted a more focused interviewing style as a result (Wolfman et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…On the one hand, the increased use of direct questions with children in the MA and ID groups, and more option-posing questions with the CWID, may reflect the interviewers' use of alternate strategies when children were not forthcoming in response to more open prompting (Gilstrap & Ceci, 2005). Open prompts are strongly promoted as the ideal interview question type because they elicit more detailed and accurate responses, but they can also be associated with more non-responding (e.g., Korkman et al, 2006;Korkman, Santtila, Wester aker, & Sandnabba, 2008;Melinder & Gilstrap, 2009;Wolfman, Brown, & Jose, 2016b). Alternatively, interviewers may have persisted with a more narrowly focussed style of questioning with the younger and more impaired groups because of assumptions about their inability to answer questions (Aarons & Powell, 2003;Aarons et al, 2004;Ericson et al, 1994;Milne, 1999;Nathanson & Platt, 2005;Phillips et al, 2012;Sharp, 2001), and usual styles of interacting with children in these groups (e.g., Agnew et al, 2006;Lamb & Brown, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in the research summarized earlier, by increasing their use of, and children's opportunities to respond to, open-ended prompting, interviewers can increase the quality of children's evidence and minimize the reporting of false details (28). In particular, cued invitations helped children elaborate on their spontaneous accounts (5), and pairing openended questions with more focused questions improved interviewing quality (29). Furthermore, in another study (30), children grasped temporal concepts more effectively than had been suggested by previous research.…”
Section: Research With the Nichd Investigative Interview Protocolmentioning
confidence: 99%